Modified cucurbit [n] uril-chitosan composite material as well as preparation method and application thereof
By modifying the cucurbit [n]urea-chitosan composite material, the problem of poor adsorption performance of existing adsorbents under acidic conditions is solved, and efficient adsorption and recycling of heavy metal ions is achieved.
Patent Information
- Application Number
- CN202411576783.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-28
AI Technical Summary
When treating dye wastewater, existing adsorbents have limited adsorption capacity and poor regeneration performance, making it difficult to effectively remove heavy metal ions, especially under acidic conditions.
By combining cucurbita with chitosan and modifying it through cross-linking and grafting reactions, a modified cucurbita-chitosan composite material is formed to enhance its adsorption performance and stability.
When treating wastewater containing heavy metal ions, the modified composite material exhibits good adsorption performance and stability, can efficiently adsorb a variety of heavy metal ions, and can be recycled.
Smart Images

Figure CN119529330A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, and in particular to a modified cucurbit[n]uril-chitosan composite material and a preparation method and application thereof. Background Art
[0002] With the vigorous development of the printing and dyeing industry, the environmental pollution caused by dyes and heavy metal ions in discharged industrial wastewater has become increasingly prominent. The composition of dye wastewater is complex, the concentration is high, the color is dark and it is difficult to degrade, which has a serious impact on the environment. The methods commonly used for the treatment of printing and dyeing wastewater are physical, chemical and biological. Among them, the adsorption method in the physical method is the most common method. Due to the limited adsorption capacity and poor regeneration performance of the current adsorbent, the development of efficient, economical and renewable adsorbents is an important research hotspot.
[0003] Cucurbit[n]uril is a cyclic compound prepared by the reaction of glycoluril and formaldehyde under acidic conditions. It is pumpkin-shaped and has a rigid cavity structure with a completely symmetrical hydrophilic exterior and hydrophobic interior. With the gradual deepening of research on cucurbit[n]uril, on the basis of separating cucurbit[5]uril (CB[5]), cucurbit[6]uril (CB[6]), cucurbit[7]uril (CB[7]) and cucurbit[8]uril (CB[8]), cucurbit
[10] uril (CB
[10] ) was further separated, expanding the family of cucurbit[n]uril. Since the port of cucurbit[n]uril is composed of polar carbonyl groups, it can coordinate with heavy metal ions to achieve efficient adsorption of heavy metals. However, the reusability of cucurbit[n]uril is poor, which to some extent restricts its application as an adsorbent. Finding an effective regeneration method to make cucurbit[n]uril recyclable will be the key to using cucurbit[n]uril as an adsorbent material.
[0004] Chitosan, as the second most abundant polysaccharide in the world, contains abundant amino and hydroxyl groups, has the advantages of wide sources, low cost, non-toxicity, good biocompatibility, etc., and is widely used in adsorption. Chitosan is alkali-resistant but not acid-resistant, and has poor adsorption effect on high concentrations of dyes and heavy metal ions, which limits its application as an adsorbent. Modifying chitosan to make it stable under acidic conditions and have good adsorption performance is one of the research purposes of the present invention. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a method for preparing a modified cucurbit[n]uril-chitosan composite material. The method has a simple process and mild process conditions. The modified cucurbit[n]uril-chitosan composite material prepared by the method has good adsorption performance for heavy metal ions, and the composite material can be recycled.
[0006] In order to achieve the above object, the present invention provides a method for preparing a modified cucurbit [n] uril-chitosan composite material, which comprises:
[0007] (1) dispersing cucurbitac[n]uril in a chitosan solution to obtain a dispersed system;
[0008] (2) subjecting the dispersed system obtained in step (1) to a primary crosslinking reaction with an aqueous solution of sodium tripolyphosphate, and then performing solid-liquid separation and collecting the solid phase material;
[0009] (3) subjecting the solid phase material obtained in step (2) to a secondary crosslinking reaction with epichlorohydrin in an alkaline aqueous solution, and then performing solid-liquid separation and collecting the solid phase material;
[0010] (4) subjecting the solid phase material obtained in step (3) to a graft reaction with an aqueous solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and disodium ethylenediaminetetraacetate, and then subjecting the solid-liquid separation to freeze-drying the obtained solid phase material;
[0011] Wherein, in step (1), the cucurbit[n]uril is cucurbit[5]uril, cucurbit[6]uril, cucurbit[7]uril or cucurbit[8]uril;
[0012] The weight ratio of the disodium ethylenediaminetetraacetic acid to the chitosan is 1:0.2-1.5.
[0013] Preferably, in step (1), the weight ratio of cucurbit[n]uril to chitosan is 0.1 to 1:1.
[0014] Preferably, in step (2), the concentration of the sodium tripolyphosphate aqueous solution is 0.5 to 3 wt %; and / or
[0015] In step (2), the time of the primary cross-linking reaction is 6 to 12 hours.
[0016] Preferably, the volume ratio of epichlorohydrin to the weight ratio of chitosan is 1-5 mL:15 g; and / or
[0017] In step (3), the pH value of the alkaline aqueous solution is 10 to 14; and / or
[0018] In step (3), the secondary cross-linking reaction time is 2 to 6 hours.
[0019] Preferably, in step (4), the weight ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the N-hydroxysuccinimide is 1:1-2; and / or
[0020] In step (4), the weight ratio of the total weight of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and the N-hydroxysuccinimide to the disodium ethylenediaminetetraacetate is 3:5-20.
[0021] Preferably, in step (4), the grafting reaction conditions include: a time of 2 to 3 hours; and / or
[0022] In step (4), the freeze-drying conditions include: temperature of -70 to -50°C and time of 10 to 16 hours.
[0023] The second aspect of the present invention provides a modified cucurbit[n]uril-chitosan composite material prepared by the above method.
[0024] The third aspect of the present invention provides the use of the modified cucurbit[n]uril-chitosan composite material in treating wastewater containing heavy metal ions.
[0025] Preferably, the heavy metal ions are selected from Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ One or more of the following.
[0026] Preferably, the heavy metal ion is Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ combination.
[0027] Preferably, in the wastewater containing heavy metal ions, Hg 2+ The concentration is 50~800mg / L, Cu 2+ The concentration is 50~500mg / L, Cr 3+ The concentration is 50~700mg / L, Pb 2+ The concentration is 50-600 mg / L.
[0028] The modified cucurbitac[n]uril-chitosan composite material (EDTA-CB[n]-CS) prepared by the method of the present invention has good adsorption performance for heavy metal ions, has a high maximum adsorption capacity for a single heavy metal ion, and can also adsorb multiple heavy metal ions at the same time with a high equilibrium adsorption capacity of various heavy metal ions, especially for heavy metal ions containing Hg 2+ , Cu 2+ Cr 3+ and Pb 2+The sewage treatment effect is good; at the same time, the modified cucurbit [n] uril-chitosan composite material can be recycled and has good adsorption stability. This is mainly because a bead-shaped composite material (CB[n]-CS) in which cucurbit [n] uril is wrapped by chitosan (CS) is obtained through a primary cross-linking reaction, which has a large specific surface area and good adsorption performance. At the same time, cucurbit [n] uril is converted from a powder that is difficult to recycle to make it dispersed inside the chitosan aerogel beads modified with ethylenediaminetetraacetic acid to make it easy to regenerate; then a secondary cross-linking reaction is performed to make the cyclic Oxychloropropane forms a chemical crosslink with chitosan, and the porosity and mechanical properties of the chitosan are enhanced, thereby enhancing the adsorption performance and adsorption stability of the chitosan. Finally, disodium ethylenediaminetetraacetate (Na2EDTA) is grafted onto the surface of chitosan in the form of ethylenediaminetetraacetic acid through a grafting reaction to modify the chitosan. Based on the compounding of chitosan (CS), cucurbitac[n]urea and disodium ethylenediaminetetraacetate and the quantitative relationship between chitosan and disodium ethylenediaminetetraacetate, the modified cucurbitac[n]urea-chitosan composite material has good adsorption performance and cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the infrared spectra of CB[6], CS, Na2EDTA, CB[n]-CS and EDTA-CB[n]-CS in Example 1 of the present invention;
[0030] Figure 2 is a scanning electron microscope image of the modified cucurbit[n]uril-chitosan composite material prepared in Example 1 of the present invention;
[0031] Figure 3 is a Zeta potential diagram of the modified cucurbit[n]uril-chitosan composite material prepared in Example 1 of the present invention;
[0032] Figure 4 is the isothermal adsorption curve of heavy metal ions by the modified cucurbit[n]uril-chitosan composite material prepared in Example 1 of the present invention;
[0033] Figure 5 This is a cycle performance diagram of the modified cucurbit[n]uril-chitosan composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0035] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0036] In one aspect, the present invention provides a method for preparing a modified cucurbit[n]uril-chitosan composite material, the method comprising:
[0037] (1) dispersing cucurbitac[n]uril in a chitosan solution to obtain a dispersed system;
[0038] (2) subjecting the dispersed system obtained in step (1) to a primary crosslinking reaction with an aqueous solution of sodium tripolyphosphate, and then performing solid-liquid separation and collecting the solid phase material;
[0039] (3) subjecting the solid phase material obtained in step (2) to a secondary crosslinking reaction with epichlorohydrin in an alkaline aqueous solution, and then performing solid-liquid separation and collecting the solid phase material;
[0040] (4) subjecting the solid phase material obtained in step (3) to a graft reaction with an aqueous solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and disodium ethylenediaminetetraacetate, and then subjecting the solid-liquid separation to freeze-drying the obtained solid phase material;
[0041] Wherein, in step (1), the cucurbit[n]uril is cucurbit[5]uril, cucurbit[6]uril, cucurbit[7]uril or cucurbit[8]uril;
[0042] The weight ratio of the disodium ethylenediaminetetraacetic acid to the chitosan is 1:0.2-1.5.
[0043] In a preferred embodiment, in order to further improve the adsorption performance of the modified cucurbit[n]uril-chitosan composite material, the weight ratio of the disodium ethylenediaminetetraacetic acid to the chitosan is 1:0.3-0.75.
[0044] In the present invention, step (1) allows cucurbitacin [n] uril to be uniformly dispersed in a chitosan (CS) solution to form a uniform and stable dispersion system; step (2) allows the uniform and stable dispersion system formed in step (1) to form a bead-shaped composite material (CB[n]-CS) in which cucurbitacin [n] uril is wrapped by chitosan through a primary cross-linking reaction of sodium tripolyphosphate, which has a large specific surface area and good adsorption performance; step (3) allows the secondary cross-linking reaction of epichlorohydrin to form a chemical cross-link between epichlorohydrin and chitosan, thereby enhancing its porosity and mechanical properties, and further enhancing its adsorption performance and adsorption stability; step (4) allows ethylenediaminetetraacetic acid to be grafted onto the surface of chitosan, thereby modifying its surface and further enhancing its adsorption performance; and finally, freeze-drying is performed to form a bead-shaped ethylenediaminetetraacetic acid-modified cucurbitacin [n] uril-chitosan composite material (EDTA-CB[n]-CS) having a wrinkled surface. The composite material has good adsorption performance and adsorption stability for heavy metal ions and can be recycled.
[0045] In the present invention, there is no special requirement for the solid-liquid separation method, and any method conventionally used in the art can be used, for example, filtration.
[0046] In the present invention, in step (1), the cucurbit[n]uril is prepared by a conventional method in the art, and then separated by a brine separation method to obtain cucurbit[5]uril (CB[5]), cucurbit[6]uril (CB[6]), cucurbit[7]uril (CB[7]) and cucurbit[8]uril (CB[8]).
[0047] In the present invention, in step (1), the chitosan solution is obtained by mixing chitosan and an acidic solution, and the acid in the acidic solution is selected from one or more of acetic acid, formic acid and hydrochloric acid; in the most preferred embodiment, the concentration of the acidic solution is 1 to 3 wt%, and the acid in the acidic solution is acetic acid.
[0048] In the present invention, in step (1), there is no special requirement for the concentration of the chitosan solution, as long as the chitosan can be completely dissolved.
[0049] In a preferred embodiment, in order to improve the adsorption performance of the modified cucurbit[n]uril-chitosan composite material, in step (1), the weight ratio of the amount of cucurbit[n]uril to chitosan is 0.1-1:1; preferably, the weight ratio of the amount of cucurbit[n]uril to chitosan is 0.1-0.7:1; more preferably, the weight ratio of the amount of cucurbit[n]uril to chitosan is 0.3-0.65:1; specifically, the weight ratio of the amount of cucurbit[n]uril to chitosan can be 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1 or 0.65:1.
[0050] In a preferred embodiment, in order to further improve the adsorption performance of the modified cucurbit[n]uril-chitosan composite material, in step (2), the concentration of the sodium tripolyphosphate aqueous solution is 0.5-3wt%; preferably, the concentration of the sodium tripolyphosphate aqueous solution is 1-3wt%.
[0051] In a preferred embodiment, in step (2), the time of the primary cross-linking reaction is 6 to 12 hours; preferably, the time of the primary cross-linking reaction is 8 to 12 hours.
[0052] In the present invention, the step (2) further comprises washing the collected solid phase material until the washing solution is neutral.
[0053] In a preferred embodiment, in order to further improve the adsorption performance and adsorption stability of the modified cucurbitac[n]urea-chitosan composite material, the ratio of the volume of epichlorohydrin to the weight of chitosan is 1-5 mL:15 g; preferably, the ratio of the volume of epichlorohydrin to the weight of chitosan is 2-4 mL:15 g.
[0054] In a preferred embodiment, in order to increase the degree of chemical crosslinking between epichlorohydrin and chitosan, in step (3), the pH value of the alkaline aqueous solution is 10-14; preferably, the pH value of the alkaline aqueous solution is 11-13.
[0055] In the present invention, there is no special requirement for the alkaline substance in the alkaline aqueous solution, as long as its pH value can reach 10 to 14; preferably, the alkaline substance in the alkaline aqueous solution is an inorganic base and / or a weak acid and strong base salt; in a preferred embodiment, the alkaline substance is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.
[0056] In a preferred embodiment, in step (3), the secondary cross-linking reaction time is 2 to 6 hours; preferably, the secondary cross-linking reaction time is 2 to 4 hours.
[0057] In the present invention, the step (3) further comprises washing the collected solid phase material until the washing solution is neutral.
[0058] In a preferred embodiment, in order to improve the modification effect of EDTA on chitosan, in step (4), the weight ratio of the amount of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to the amount of N-hydroxysuccinimide is 1:1-2; the 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and the N-hydroxysuccinimide are used as condensation agents, so that disodium EDTA is grafted on the surface of chitosan in the form of EDTA to achieve modification of the chitosan surface and improve its adsorption performance.
[0059] In a preferred embodiment, in order to further improve the modification effect of EDTA on chitosan, in step (4), the weight ratio of the total weight of the 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and the N-hydroxysuccinimide to the disodium EDTA is 3:5 to 20.
[0060] In a preferred embodiment, in step (4), the conditions of the grafting reaction include: time is 2 to 3 hours.
[0061] In a preferred embodiment, in step (4), the freeze-drying conditions include: a temperature of -70°C to -50°C and a time of 10 to 16 hours.
[0062] In the present invention, the step (4) further comprises washing the collected solid phase material before freeze drying until the washing solution is neutral.
[0063] In the present invention, in step (4), there is no special requirement for the concentration of the aqueous solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and disodium ethylenediaminetetraacetate, as long as 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and disodium ethylenediaminetetraacetate can be dissolved.
[0064] In the present invention, in step (2), step (3) and step (4), the primary cross-linking reaction, the secondary cross-linking reaction and the grafting reaction are all carried out at room temperature (10 to 35° C.).
[0065] The second aspect of the present invention provides a modified cucurbit[n]uril-chitosan composite material prepared by the above method.
[0066] The modified cucurbit[n]uril-chitosan composite material prepared by the method of the present invention has good adsorption performance for heavy metal ions, and the composite material can also be recycled and has good adsorption stability.
[0067] The third aspect of the present invention provides the use of the modified cucurbit[n]uril-chitosan composite material in treating wastewater containing heavy metal ions.
[0068] The modified cucurbitac[n]uril-chitosan composite material of the present invention is not only for the 2+ , Cu 2+ Cr 3+ and Pb 2+ It has good treatment effect on sewage containing Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ It also has a good treatment effect on sewage, and its final equilibrium adsorption capacity is high.
[0069] In a preferred embodiment, the heavy metal ion is selected from Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ One or more of the following.
[0070] In a more preferred embodiment, the heavy metal ion is Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ combination.
[0071] In a preferred embodiment, in the wastewater containing heavy metal ions, Hg 2+ The concentration is 50~800mg / L, Cu 2+ The concentration is 50~500mg / L, Cr 3+ The concentration is 50~700mg / L, Pb 2+ The concentration is 50-600 mg / L; preferably, Hg 2+ The concentration is 50~450mg / L, Cu 2+ The concentration is 50~200mg / L, Cr 3+ The concentration is 50~200mg / L, Pb 2+ The concentration is 50-500 mg / L.
[0072] The following examples further illustrate the modified cucurbit [n] uril-chitosan composite material and its preparation method and application described in the present invention. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0073] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0074] Example 1
[0075] (1) dispersing 0.25 g of cucurbit[6]uril in a chitosan solution and obtaining a dispersion system by mechanical stirring, wherein the chitosan solution is obtained by mixing 0.75 g of chitosan and 30 mL of an acetic acid solution having a mass concentration of 1%;
[0076] (2) adding the dispersed system obtained in step (1) dropwise to a sodium tripolyphosphate aqueous solution having a concentration of 1 wt%, crosslinking at a temperature of 20° C. for 8 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0077] (3) mixing the solid phase material obtained in step (2), 0.2 mL of epichlorohydrin and a sodium hydroxide aqueous solution with a pH value of 13, cross-linking at a temperature of 20° C. for 2 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0078] (4) The solid phase material obtained in step (3) was grafted with 50 mL of an aqueous solution containing 0.1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.2 g of N-hydroxysuccinimide and 2 g of disodium ethylenediaminetetraacetate at 20° C. for 2 h, and then the solid-liquid separation was performed and the obtained solid phase material was freeze-dried at -65° C. for 14 h to obtain a modified cucurbit[6]urea-chitosan composite material A1.
[0079] Example 2
[0080] (1) dispersing 0.25 g of cucurbit[5]uril in a chitosan solution and obtaining a dispersion system by mechanical stirring, wherein the chitosan solution is obtained by mixing 0.75 g of chitosan and 30 mL of an acetic acid solution having a mass concentration of 1%;
[0081] (2) adding the dispersed system obtained in step (1) dropwise to a sodium tripolyphosphate aqueous solution having a concentration of 1 wt%, crosslinking at a temperature of 20° C. for 8 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0082] (3) mixing the solid phase material obtained in step (2), 0.2 mL of epichlorohydrin and a sodium hydroxide aqueous solution with a pH value of 13, cross-linking at a temperature of 20° C. for 2 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0083] (4) The solid phase material obtained in step (3) is grafted with an aqueous solution containing 0.1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.2 g of N-hydroxysuccinimide and 2 g of disodium ethylenediaminetetraacetate at 20° C. for 2 h, and then the solid-liquid separation is performed and the obtained solid phase material is freeze-dried at -65° C. for 14 h to obtain a modified cucurbit[5]urea-chitosan composite material A2.
[0084] Example 3
[0085] (1) dispersing 0.075 g of cucurbit[6]uril in a chitosan solution and obtaining a dispersion system by mechanical stirring, wherein the chitosan solution is obtained by mixing 0.75 g of chitosan and 30 mL of an acetic acid solution having a mass concentration of 1%;
[0086] (2) adding the dispersed system obtained in step (1) dropwise to a sodium tripolyphosphate aqueous solution having a concentration of 1 wt%, crosslinking at a temperature of 20° C. for 8 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0087] (3) mixing the solid phase material obtained in step (2), 0.2 mL of epichlorohydrin and a sodium hydroxide aqueous solution with a pH value of 13, cross-linking at a temperature of 20° C. for 2 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0088] (4) The solid phase material obtained in step (3) is grafted with an aqueous solution containing 0.1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.2 g of N-hydroxysuccinimide and 2 g of disodium ethylenediaminetetraacetate at 20° C. for 2 h, and then the solid-liquid separation is performed and the obtained solid phase material is freeze-dried at -65° C. for 14 h to obtain a modified cucurbit[6]uril-chitosan composite material A3.
[0089] Example 4
[0090] (1) dispersing 0.25 g of cucurbit[6]uril in a chitosan solution and obtaining a dispersion system by mechanical stirring, wherein the chitosan solution is obtained by mixing 0.75 g of chitosan and 30 mL of an acetic acid solution having a mass concentration of 1%;
[0091] (2) adding the dispersed system obtained in step (1) dropwise to a sodium tripolyphosphate aqueous solution having a concentration of 1 wt%, crosslinking at a temperature of 20° C. for 8 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0092] (3) mixing the solid phase material obtained in step (2), 0.2 mL of epichlorohydrin and a sodium hydroxide aqueous solution with a pH value of 13, cross-linking at a temperature of 20° C. for 2 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0093] (4) The solid phase material obtained in step (3) is grafted with an aqueous solution containing 0.1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.2 g of N-hydroxysuccinimide and 0.5 g of disodium ethylenediaminetetraacetate at 20° C. for 2 h, and then the solid-liquid separation is performed and the obtained solid phase material is freeze-dried at -65° C. for 14 h to obtain a modified cucurbit[6]urea-chitosan composite material A4.
[0094] Example 5
[0095] (1) dispersing 0.25 g of cucurbit[6]uril in a chitosan solution and obtaining a dispersion system by mechanical stirring, wherein the chitosan solution is obtained by mixing 0.75 g of chitosan and 30 mL of an acetic acid solution having a mass concentration of 1%;
[0096] (2) adding the dispersed system obtained in step (1) dropwise to a sodium tripolyphosphate aqueous solution having a concentration of 1 wt%, crosslinking at a temperature of 20° C. for 8 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0097] (3) mixing the solid phase material obtained in step (2), 0.05 mL of epichlorohydrin and a sodium hydroxide aqueous solution with a pH value of 13, cross-linking at a temperature of 20° C. for 2 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0098] (4) The solid phase material obtained in step (3) is grafted with an aqueous solution containing 0.1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.2 g of N-hydroxysuccinimide and 2 g of disodium ethylenediaminetetraacetate at 20° C. for 2 h, and then the solid-liquid separation is performed and the obtained solid phase material is freeze-dried at -65° C. for 14 h to obtain a modified cucurbit[6]uril-chitosan composite material A5.
[0099] Example 6
[0100] (1) dispersing 0.25 g of cucurbit[6]uril in a chitosan solution and obtaining a dispersion system by mechanical stirring, wherein the chitosan solution is obtained by mixing 0.75 g of chitosan and 30 mL of an acetic acid solution having a mass concentration of 1%;
[0101] (2) adding the dispersed system obtained in step (1) dropwise to a sodium tripolyphosphate aqueous solution having a concentration of 1 wt%, crosslinking at a temperature of 20° C. for 8 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0102] (3) mixing the solid phase material obtained in step (2), 0.2 mL of epichlorohydrin and a sodium hydroxide aqueous solution with a pH value of 13, cross-linking at a temperature of 20° C. for 2 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0103] (4) The solid phase material obtained in step (3) was grafted with an aqueous solution containing 0.2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.4 g of N-hydroxysuccinimide and 3.75 g of disodium ethylenediaminetetraacetate at 20° C. for 2 h, and then the solid-liquid separation was performed and the obtained solid phase material was freeze-dried at -65° C. for 14 h to obtain a modified cucurbit[6]uril-chitosan composite material A6.
[0104] Comparative Example 1
[0105] The process is carried out in the same manner as in Example 1, except that in step (1), cucurbitacin[6]uril is not added.
[0106] Comparative Example 2
[0107] The process is carried out in the same manner as in Example 1, except that step (2) is not performed.
[0108] Comparative Example 3
[0109] The method is implemented in the same manner as in Example 1, except that step (3) is not performed.
[0110] Comparative Example 4
[0111] (1) dispersing 0.25 g of cucurbit[6]uril in a chitosan solution and obtaining a dispersion system by mechanical stirring, wherein the chitosan solution is obtained by mixing 0.75 g of chitosan and 30 mL of an acetic acid solution having a mass concentration of 1%;
[0112] (2) adding the dispersed system obtained in step (1) dropwise to a sodium tripolyphosphate aqueous solution having a concentration of 1 wt%, crosslinking at a temperature of 20° C. for 8 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0113] (3) mixing the solid phase material obtained in step (2), 0.2 mL of epichlorohydrin and a sodium hydroxide aqueous solution with a pH value of 13, cross-linking at a temperature of 20° C. for 2 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0114] (4) The solid phase material obtained in step (3) was grafted with 50 mL of an aqueous solution containing 0.25 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.5 g of N-hydroxysuccinimide and 5 g of disodium ethylenediaminetetraacetate at 20° C. for 2 h, and then the solid-liquid separation was performed and the obtained solid phase material was freeze-dried at -65° C. for 14 h to obtain a modified cucurbit[6]urea-chitosan composite material A10.
[0115] Comparative Example 5
[0116] (1) dispersing 0.25 g of cucurbit[6]uril in a chitosan solution and obtaining a dispersion system by mechanical stirring, wherein the chitosan solution is obtained by mixing 0.75 g of chitosan and 30 mL of an acetic acid solution having a mass concentration of 1%;
[0117] (2) mixing the dispersion obtained in step (1), 0.2 mL of epichlorohydrin and a sodium hydroxide aqueous solution with a pH value of 13, crosslinking at a temperature of 20° C. for 2 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0118] (3) adding the solid phase material obtained in step (2) to a sodium tripolyphosphate aqueous solution with a concentration of 1 wt%, cross-linking at a temperature of 20° C. for 8 h, then performing solid-liquid separation and collecting the solid phase material, and washing the collected solid phase material until the washed solution is neutral;
[0119] (4) The solid phase material obtained in step (3) was grafted with 50 mL of an aqueous solution containing 0.1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.2 g of N-hydroxysuccinimide and 2 g of disodium ethylenediaminetetraacetate at 20° C. for 2 h, and then the solid-liquid separation was performed and the obtained solid phase material was freeze-dried at -65° C. for 14 h to obtain a modified cucurbit[6]urea-chitosan composite material A11.
[0120] Test Case
[0121] (1) CB[6], CS, Na2EDTA, CB[n]-CS and EDTA-CB[n]-CS in Example 1 were characterized by Fourier transform infrared spectrometer. The results are as follows: Figure 1 As shown;
[0122] Depend on Figure 1 It can be seen that: 1745cm -1 is the carbonyl stretching vibration on CB[6], 1629 cm -1 、1396cm -1 The OCO asymmetric and symmetric stretching vibrations of the carboxylate ion on EDTA, 1147 cm -1 is the CN stretching vibration peak of CB[6], 1087 cm -1 is the CO stretching vibration of chitosan; 1475cm -1 、1363cm -1 、1317cm -1 、1294cm -1 and 1193cm -1 They can all be observed in the infrared spectrum of the modified cucurbit [6] uril-chitosan composite material A1, indicating that the modification of CB[6]-CS is successful. At the same time, the characteristic peaks of cucurbit [6] uril, chitosan and EDTA appear in the infrared spectrum of the modified cucurbit [6] uril-chitosan composite material A1, indicating that the modified cucurbit [6] uril-chitosan composite material (EDTA-CB[6]-CS) is prepared by the method described in this application.
[0123] (2) The appearance and microstructure of the modified cucurbit [6] urea-chitosan composite material A1 prepared in Example 1 were characterized. Figure 2 As shown; among them, the actual photograph of the modified cucurbit [6] uril-chitosan composite material A1 is shown in Figure 2 a; Scanning electron micrograph of the modified cucurbit[6]urea-chitosan composite material A1 (magnified 130 times) Figure 2 b; Scanning electron microscopy image of modified cucurbit[6]urea-chitosan composite material A1 (magnified 1000 times) Figure 2 c; the cross-sectional scanning electron microscopy image of the modified cucurbit[6]urea-chitosan composite material A1 is shown in Figure 2 As shown in d.
[0124] Depend on Figure 2 It can be seen from a that the modified cucurbit[6]urea-chitosan composite material A1 prepared in Example 1 is spherical and has uniform size. This spherical adsorbent is conducive to subsequent recovery and regeneration; Figure 2 b It can be seen that the modified cucurbit[6]urea-chitosan composite material A1 prepared in Example 1 maintains a spherical shape after freeze-drying, and has abundant grooves on the surface; Figure 2 c It can be seen that the surface of the modified cucurbit [6] uril-chitosan composite material A1 prepared in Example 1 is rough and wrinkled; Figure 2It can be seen from the figure that the modified cucurbit[6]uril-chitosan composite material A1 prepared in Example 1 has abundant pore structures distributed inside. This three-dimensional network structure can provide more active adsorption sites for the adsorption of heavy metal ions.
[0125] (3) The modified cucurbit[6]uril-chitosan composite material A1 prepared in Example 1 was characterized by Zeta potential test. The results are as follows: Figure 3 As shown;
[0126] Depend on Figure 3 It can be seen that the isoelectric point of the modified cucurbit [6] uril-chitosan composite material A1 is about 7.2. Under strong acidic conditions (pH = 2), its surface charge is above +20 mV. As the pH value increases, the potential of the modified cucurbit [6] uril-chitosan composite material A1 gradually decreases until it reaches 0 mV. When pH>7.2, the potential of the modified cucurbit [6] uril-chitosan composite material A1 changes from positive to negative. Under strong alkalinity (pH = 12), its surface charge reaches -15 mV. This is mainly because the hydroxyl groups on chitosan react with the H + or OH - Hydrogen bonds are formed between the uric acid and chitosan, resulting in a large amount of positive or negative charge on the surface of the modified cucurbit[6]uril-chitosan composite material A1. The adsorption of positive and negative ions can be achieved by adjusting the pH value.
[0127] (4) The heavy metal adsorption performance of the modified cucurbit [6] uril-chitosan composite material A1 prepared in Example 1 was tested. The results are as follows: Figure 4 As shown;
[0128] Depend on Figure 4 a It can be seen that EDTA-CB[6]-CSA1 has a significant effect on Hg 2+ , Cu 2+ Cr 3+ , Pb 2+ The Sips isotherm model belongs to the mixed model of Langmuir and Freundlich. The R of the Sips isotherm model is 2 This indicates that the Sips isotherm model can better describe the adsorption equilibrium data. 2+ , Cu 2+ Cr 3+ and Pb 2+ The maximum adsorption capacity (qmax) of EDTA-CB[6]-CSA1 for heavy metal ions Hg 2+ , Cu 2+ Cr3+ and Pb 2+ Has a higher maximum adsorption capacity.
[0129] (5) The adsorption stability of the sample prepared in Example 1 was tested. 2+ 50 mL of simulated wastewater with a concentration of 100 mg / L was adsorbed. After 10 h of adsorption, the adsorbed sample was desorbed using sodium hydroxide solution. This cycle was repeated 5 times. The removal rate is as follows: Figure 5 As shown;
[0130] Depend on Figure 5 It can be seen that in the 5 cycles, EDTA-CB[6]-CSA1 has a significant effect on Pb 2+ The final removal rate was still as high as 76.9%, which shows that EDTA-CB[6]-CSA1 is easy to regenerate and has good 2+ The removal rate is high.
[0131] (6) The adsorption performance of the samples prepared in the embodiment and the comparative example was tested. The samples were added to simulated wastewater containing the same concentration of heavy metal examples, ultrasonicated for 10 minutes, and the supernatant was taken after adsorption for 10 hours. The concentration of the supernatant was measured by ICP-AES, and the removal rate and adsorption amount were calculated according to formula (1) and formula (2), respectively;
[0132] Removal rate = (C0-C e ) / C0*100% (1)
[0133] Adsorption amount = (C0-C e )*V / m (2)
[0134] Where: In formula (1) and formula (2), C0 is the initial concentration of the solution, C e is the equilibrium concentration of the solution, in mg / L; m is the mass of the sample, in mg; V is the volume of the simulated wastewater, in L; the mass of the sample used is 15 mg, and the volume of the simulated wastewater is 50 mL; Hg in the simulated wastewater 2+ , Cu 2+ Cr 3+ and Pb 2+ The concentrations of the two compounds are all 100 mg / L. The calculation results are shown in Table 1.
[0135] Table 1
[0136]
[0137] "-" in the table means that the sample was not synthesized and the data could not be measured
[0138] The results in Table 1 show that the modified cucurbit[n]uril-chitosan composite material prepared by the method of the present invention has good 2+ , Cu 2+ Cr 3+ and Pb 2+ When treating wastewater containing four heavy metal ions, the modified cucurbit[n]uril-chitosan composite material has a significant effect on Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ All of them have removal effects, among which the modified cucurbit[n]uril-chitosan composite material is effective for removing Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ When treating wastewater containing four heavy metal ions, Hg 2+ and Pb 2+ The adsorption capacity of Cu 2+ and Cr 3+ The adsorption capacity is 85 mg / g and above.
[0139] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a modified cucurbit[n]uril-chitosan composite material, characterized in that: The method includes: (1) dispersing cucurbitac[n]uril in a chitosan solution to obtain a dispersed system; (2) subjecting the dispersed system obtained in step (1) to a primary crosslinking reaction with an aqueous solution of sodium tripolyphosphate, and then performing solid-liquid separation and collecting the solid phase material; (3) subjecting the solid phase material obtained in step (2) to a secondary crosslinking reaction with epichlorohydrin in an alkaline aqueous solution, and then performing solid-liquid separation and collecting the solid phase material; (4) subjecting the solid phase material obtained in step (3) to a graft reaction with an aqueous solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and disodium ethylenediaminetetraacetate, and then subjecting the solid-liquid separation to freeze-drying the obtained solid phase material; Wherein, in step (1), the cucurbit[n]uril is cucurbit[5]uril, cucurbit[6]uril, cucurbit[7]uril or cucurbit[8]uril; The weight ratio of the disodium ethylenediaminetetraacetic acid to the chitosan is 1:0.2-1.
5.
2. The method according to claim 1, characterized in that In step (1), the weight ratio of cucurbit[n]uril to chitosan is 0.1 to 1:
1.
3. The method according to claim 1 or 2, characterized in that: In step (2), the concentration of the sodium tripolyphosphate aqueous solution is 0.5 to 3 wt %; and / or In step (2), the time of the primary cross-linking reaction is 6 to 12 hours.
4. The method according to claim 3, characterized in that The ratio of the volume of epichlorohydrin to the weight of chitosan is 1-5 mL:15 g; and / or In step (3), the pH value of the alkaline aqueous solution is 10 to 14; and / or In step (3), the secondary cross-linking reaction time is 2 to 6 hours.
5. The method according to claim 1 or 4, characterized in that: In step (4), the weight ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the N-hydroxysuccinimide is 1:1-2; and / or In step (4), the weight ratio of the total weight of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and the N-hydroxysuccinimide to the disodium ethylenediaminetetraacetate is 3:5-20.
6. The method according to claim 5, characterized in that In step (4), the grafting reaction conditions include: a time of 2 to 3 hours; and / or In step (4), the freeze-drying conditions include: temperature of -70 to -50°C and time of 10 to 16 hours.
7. The modified cucurbit[n]uril-chitosan composite material prepared by the method according to any one of claims 1 to 6.
8. Use of the modified cucurbit[n]uril-chitosan composite material according to claim 7 in treating wastewater containing heavy metal ions.
9. The use according to claim 8, characterized in that: The heavy metal ion is selected from Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ One or more of the following.
10. The use according to claim 9, characterized in that: The heavy metal ion is Hg 2+ , Cu 2+ Cr 3+ and Pb 2+ combination of; Preferably, in the wastewater containing heavy metal ions, Hg 2+ The concentration is 50~800mg / L, Cu 2+ The concentration is 50~500mg / L, Cr 3+ The concentration is 50~700mg / L, Pb 2+ The concentration is 50-600 mg / L.
Citation Information
Patent Citations
Preparation method of ethylenediamine tetraacetic acid modified magnetic attapulgite-chitosan microspheres
CN111282551A
Cucurbit[n]uril-chitosan composite bead, preparation method and application thereof
CN113828282A
Modified cucurbit [n] uril-chitosan composite aerogel bead as well as preparation method and application thereof
CN115254043A